"In Universities, the Religious People Keep Their Mouths Shut": Solving an Interdiscursive Problem in Higher Education Literacy Practices - Smith, Paul Vincent (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2022)
Religious faith, despite being a protected characteristic under UK law, is under-studied in higher education. In this article, I answer the call for studies that demonstrate the difference that religious adherence can make to the student experience of higher education instruction and assessment. In my qualitative study, I used ideas from ethnomethodology, FOUCAULT's archaeological work, academic literacies, and the Wittgensteinian perspective of WINCH to characterise the meeting of religious faith and sociological constructionism as a discursive problem occasioned by a born-again Christian student. I show how this discursive problem was described after it had been solved, pragmatically if not academically, in the student's writing. The solution comprised an interdiscursive technique of presenting faith-inspired ideas without pressing them into the service of an argument structure. My analysis of materials demonstrates a series of considerations that would not be relevant to non-religious students.